Найдите производную функции h(x)=3/x        v(h)=-1/h+3h                f(x)=2/3x+3x^2 f(x)=x^3(5x-1)(1-2x)

Найдите производную функции h(x)=3/x        v(h)=-1/h+3h                f(x)=2/3x+3x^2 f(x)=x^3(5x-1)(1-2x)
Гость
Ответ(ы) на вопрос:
Гость
1)h'(x)=(3/x)'=-3/x^2 2)v'(h)=(-1/h+3h)'=1/h^2+3 3)f'(x)=(2/3x+3x^2)'=-2/3x^2+6x 4)f'(x)=(x^3(5x-1)(1-2x))'=3x^2*(5x-1)(1-2x)+(5-20x+2)*x^3=15x^3-30x^4-3x^2+6x^3+5x^3-20x^4+2x^3=28x^3-50x^4-3x^2       
Гость
[latex]h'(x)=(\frac{3}{x})'=\frac{-3}{x^2}[/latex]    [latex]v'(h)=(-\frac{1}{h}+3h)'=\frac{1}{h^2}+3[/latex]    [latex] f'(x)=(\frac{2}{3x}+3x^2)'=-\frac{2}{3x^2}+6x[/latex]   [latex]f'(x)=(x^3(5x-1)(1-2x))'=(x^3)'(5x-1)(1-2x)+ [/latex] [latex]+x^3(5x-1)'(1-2x)+x^3(5x-1)(1-2x)'=[/latex] [latex]=3x^2(5x-1)(1-2x)+x^3*5(1-2x)+x^3(5x-1)(-2)=[/latex] [latex]=3x^2(3x-1)+5x^3-10x^4-10x^4+2x^3=[/latex] [latex]=9x^3-3x^2+5x^3-10x^4-10x^4+2x^3=16x^3-20x^4-3x^2[/latex]      
Не нашли ответ?
Ответить на вопрос
Похожие вопросы